Prognostic Value of microRNA 502 Binding Site SNP in the 3′-Untranslated Region of the SET8 Gene in Patients with Non-Hodgkin's Lymphoma. Issue 5 (September 2014) - Diao, Lanping; Su, Huiling; Wei, Guangchuan; Li, Tao; Gao, Yuhuan; Zhao, Guimin; Guo, Zhanjun
Aims and Background: A number of important cancer-associated covalent modifications of histone genes can be regulated by microRNAs (miRNAs) that bind to their target sites in the 3′-untranslated regions. We evaluated the effect of single-nucleotide polymorphisms (SNPs) at the miR-502 binding site in the 3′-untranslated region of the SET8 gene on the clinical outcome of non-Hodgkin's lymphomas (NHL). Methods and Study Design: The miR-502 binding site SNP of rs16917496 in the 3′-untranslated region of SET8 was genotyped with the ligation detection reaction method. The association of rs16917496 with NHL survival was calculated with the log-rank test using the Kaplan-Meier method. Multivariate survival analysis was performed using a Cox proportional hazards model. Results: Patients carrying the rs16917496 CC genotype had a significantly longer survival time than patients carrying the CT genotype (P = 0.043) or TT genotype (P = 0.086). In addition, rs16917496 was associated independently with the survival of NHL patients in multivariate analysis (CC vs TT, 95% CI: 1.021–3.279, RR: 1.829, P = 0.043; CC vs CT, 95% CI: 1.026–3.339, RR: 1.851, P = 0.041). The association of rs16917496 with NHL survival was further identified in the peripheral T cell lymphoma (pTCL) subtype of NHL at borderline statistically significant levels (P = 0.069). Conclusion: Our study provides evidence that the SNP in the miRNA binding site of the SET8 3′-untranslated region seems to influence survival of NHL. It may have possible prognostic and survival value in the clinic.